A quiet place. Part II [videorecording (Blu-Ray)] - Krasinski, John, 1979-; Krasinski, John, 1979-; Blunt, Emily; Murphy, Cillian, 1976-; Simmonds, Millicent, 2003-; Jupe, Noah, 2005-; Hounsou, Djimon, 1964- (Paramount, 2021)
Following the death of Lee and armed with the new weapon discovered by Reagan, the Abbots must venture off the sand path with the newest member of their family in order to protect themselves and offer a solution to the outside world. They soon are faced with the grim reality that the invading creatures are not the only threats lurking in the unknown.